A distinct variant of the SzM protein of Streptococcus equi subsp. zooepidemicus recruits C1q independent of IgG binding and inhibits activation of the classical complement pathway - René Bergmann; Wieland Schroedl; Uwe Müller; Christoph Georg Baums (Virulence, 2023)
Streptococcus equi subsp. zooepidemicus (SEZ) is a major equine pathogen that causes pneumonia, abortion, and polyarthritis. It can also cause invasive infections in humans. SEZ expresses the M-like protein SzM, which recruits host proteins such as fibrinogen to the bacterial surface. Equine SEZ strain C2, which binds only comparably low amounts of human fibrinogen in comparison to human SEZ strain C33, was previously shown to proliferate in equine and human blood. As the expression of SzM_C2 was necessary for survival in blood, this study investigated the working hypothesis that SzM_C2 inhibits complement activation through a mechanism other than fibrinogen and non-immune immunoglobulin binding. Loss-of-function experiments showed that SEZ C2, but not C33, binds C1q via SzM in IgG-free human plasma. Furthermore, SzM C2 expression is necessary for recruiting purified human or equine C1q to the bacterial surface. Flow cytometry analysis demonstrated that SzM expression in SEZ C2 is crucial for the significant reduction of C3b labelling in human plasma. Addition of human plasma to immobilized rSzM_C2 and immobilized aggregated IgG led to binding of C1q, but only the latter activated the complement system, as shown by the detection of C4 deposition. Complement activation induced by aggregated IgG was significantly reduced if human plasma was pre-incubated with rSzM_C2. Furthermore, rSzM_C2, but not rSzM_C33, inhibited the activation of the classical complement pathway in human plasma, as determined in an erythrocyte lysis experiment. In conclusion, the immunoglobulin-independent binding of C1q to SzM_C2 is associated with complement inhibition.